Lab to Farm: Applying Research on Plant Genetics and Genomics to Crop Improvement - Ronald, Pamela C. (PLoS biology, 2014)
Over the last 300 years, plant science research has provided important knowledge and technologies for advancing the sustainability of agriculture. In this Essay, I describe how basic research advances have been translated into crop improvement, explore some lessons learned, and discuss the potential for current and future contribution of plant genetic improvement technologies to continue to enhance food security and agricultural sustainability.